1998
DOI: 10.1046/j.1471-4159.1998.71031158.x
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Administration of the Neurotensin Receptor Antagonist SR 48692 Differentially Regulates Mesocortical and Mesolimbic Dopaminergic Systems

Abstract: Abstract:The purpose of the present study was to investigate the effects of repeated administration of the neurotensin receptor antagonist, SR 48692, on the activity of the mesocortical and mesolimbic dopaminergic (DA) systems. We showed that daily administration of SR 48692 for 15 days (1 mg/kg i.p.) to Wistar rats increased the expression of tyrosine hydroxylase mRNA and protein in the ventral mesencephalon. Simultaneous in vivo microdialysis in the shell part of the nucleus accumbens (AcbSh) and the medial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Ex vivo studies reported NT action on dopamine release in dopaminergic neurons (Brouard et al, 1994). Furthermore, our laboratory has previously demonstrated that in the nucleus accumbens and the mesencephalon, a chronic treatment with a NT-1 receptor antagonist increased TH expression with a loss of dopamine levels (Azzi et al, 1998). Under the same experimental conditions, NT-1 receptor antagonist treatment was also associated with a major increase of NT-1 receptor expression (Azzi et al, 1994).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Ex vivo studies reported NT action on dopamine release in dopaminergic neurons (Brouard et al, 1994). Furthermore, our laboratory has previously demonstrated that in the nucleus accumbens and the mesencephalon, a chronic treatment with a NT-1 receptor antagonist increased TH expression with a loss of dopamine levels (Azzi et al, 1998). Under the same experimental conditions, NT-1 receptor antagonist treatment was also associated with a major increase of NT-1 receptor expression (Azzi et al, 1994).…”
Section: Discussionmentioning
confidence: 92%
“…The vast majority of the NT effects are mediated through a specific high-affinity NT receptor (NT-1 receptor), belonging to the G protein coupled receptor family (Tanaka et al, 1990). NT is very effective in enhancing [ decreased dopamine release in the nucleus accumbens and in the dopamine rich regions of the rat central nervous system (Azzi et al, 1998). Interestingly, NT acts equally well on TH expression and TH activity, because NT increases protein and mRNA in neuroblastoma cell lines (Najimi et al, 1998), and TH activity via a protein kinase C pathway in cultured tuberoinfundibular dopaminergic neurons (Berry and Gudelsky, 1992).…”
mentioning
confidence: 99%
“…Chronic administration of SR-48692, which is a nonpeptide and a high-affinity NT 1 receptor antagonist with agonist activity at NT 2 receptors, can decrease methamphetamine-induced dopamine release in the nucleus accumbens, 340 suggesting this compound could also have antipsychotic-like effects.…”
Section: Noradrenergic Agentsmentioning
confidence: 99%
“…Microinjection of NT into the VTA, produces a dose-dependent in vivo DA release in the nucleus accumbens and also causes a dose-dependent circling behavior (Steinberg et al 1995). Moreover, blockade of NT receptors by the NT receptor antagonist SR 48692 decreases basal extracellular levels of DA and its metabolites in the nucleus accumbens, suggesting that NT modulates the mesolimbic DA system (Azzi et al 1998). Neurotensin has also been shown to mimic the effects of neuroleptic drugs in behavioral models of antipsychotic drug action.…”
mentioning
confidence: 99%